UV-irradiating synthesis of cyclodextrin–silver nanocluster decorated TiO2 nanoparticles for photocatalytic enhanced anticancer effect on HeLa cancer cells - Wang, Hongying; Xing, Ze; Sun, Yan; Jing, Yingjie; Zhang, Jian; Li, Xinyao; Zhang, Hailiang; Shakoor, Adnan; Guo, Junsheng (Frontiers in Chemistry, 2022)
Titanium dioxide (TiO2) has emerged as a viable choice for several biological and environmental applications because of its high efficiency, cheap cost, and high photostability. In pursuit of this purpose, the research of its many forms has been influenced by these unique aspects. The development of novel TiO2-based hybrid materials with enhanced photocatalytically induced anticancer activity has gained tremendous attention. Here, we have developed a novel photocatalytic material (TiO2–Ag NPs@-CD) by decorating ultrasmall silver nanoparticles (Ag NPs) with per-6-thio-β-cyclodextrin (SH-β-CD) on TiO2 NPs. TiO2–Ag NPs@-CD were characterized by employing various characterization techniques and evaluated for their anticancer activity against HeLa cancer cells using an MTT assay. The biocompatibility of the designed nanoparticles was determined on two normal cell lines, namely, 3T3 and hMSCs. The results show that the TiO2–Ag NPs@-CD induced superior cytotoxic effects on HeLa cancer cells at a concentration of 64 µg/mL. Live-dead staining and oxidative stress investigations demonstrated that cell membrane disintegration and ROS-induced oxidative stress generated by TiO2-Ag NPs@-CD inside HeLa cancer cells are the contributing factors to their exceptional anti-cancer performance. Moreover, TiO2-Ag NPs@-CD exhibited good biocompatibility with 3T3 and hMSCs. These results indicated that the combination of all three components—a silver core, SH-β-CD ligands, and TiO2 nanoparticles—produced a synergistic anticancer effect. Hence, the TiO2-Ag NPs@-CD is a promising material that can be employed for different biological applications.